Designing Smart and Resilient Cities for a Post-Pandemic World : Metropandemic Revolution. - Larsson, Anthony; Hatzigeorgiou, Andreas (Milton : Taylor & Francis Group, 2022)
Through a series of investigative studies, this book critically discusses and compares different cases, innovations and approaches as to how cities can utilise nascent and future digital technology and new strategies in order to build stronger resilience to better tackle comparable large-scale pandemics and future disruptions.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books